Physical Characteristics of Clove Essential Oil Microemulsions: Comparison of PIC and Spontaneous Techniques with High Energy and Low Energy Methods - Nugroho, Nazih Basuki; Sugihartini, Nining; Setianto, Arif Budi (Universitas Muhammadiyah Surakarta, 2025)
Clove flower essential oil (CFEO), which is useful as an anti-inflammatory, has characteristics that make it easily oxidised and sensitive to heat, so it is formulated in the form of a microemulsion preparation. This study aims to compare the effects of the Phase Inversion Composition (PIC) technique and spontaneous emulsification on the physical characteristics of microemulsions made using high and low-energy methods. The research began with the formulation of clove flower essential oil using the PIC technique and spontaneous emulsification based on the optimal composition from previous studies. The microemulsion was prepared at a stirring speed of 3600 rpm for high-energy and 360 rpm for low-energy. The parameters analysed included globule size, polydispersity index, viscosity, and physical stability against phase separation using centrifugation at 3500 rpm for 30 minutes. The results showed that in the high-energy method, the globule size and viscosity between the two techniques were not significantly different (p > 0.05), but the polydispersity index value in the PIC technique was lower than in spontaneous emulsification (p < 0.05), indicating a more uniform droplet distribution. In the low-energy method, the PIC technique significantly produced smaller droplet size, lower polydispersity index, and higher viscosity (p < 0.05), indicating better kinetic stability. Physical stability testing showed that all formulations remained homogeneous without phase separation. Overall, the PIC technique demonstrated superiority and consistency in producing more homogeneous and stable microemulsions. The low-energy method remains an economical and efficient alternative with proper surfactant composition optimisation.